If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + -26) = 180 Reorder the terms: x + (-26 + x) = 180 Remove parenthesis around (-26 + x) x + -26 + x = 180 Reorder the terms: -26 + x + x = 180 Combine like terms: x + x = 2x -26 + 2x = 180 Solving -26 + 2x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + 2x = 180 + 26 Combine like terms: -26 + 26 = 0 0 + 2x = 180 + 26 2x = 180 + 26 Combine like terms: 180 + 26 = 206 2x = 206 Divide each side by '2'. x = 103 Simplifying x = 103
| 1h+1+2h+1=6h+6-1h+2 | | 5+9y=5y+5 | | x(y-3)=40 | | 5x+4=23 | | 2c/11=(c-3)/4 | | 8=-2x+4-2 | | 2x-1=24.5 | | 5+x=5y+5 | | x^2-10x+10= | | 2c/11=c-3/4 | | 6+3x=11-2x | | 256=6x-4(-4x-20) | | 9y+5=5y | | k-76.98=43.56 | | x=9y | | 20x+15-5=180 | | 65+x+x-5=180 | | 3y-9+y+45=5y+40-3y | | 9x+5=5y+5 | | -1=6a-1+6a | | 0.6x-3.9=0.6 | | -8k+26=-8k | | -.5(16-2h)=11 | | 2y+19+y=7y-9 | | 3(x-5)+1=(1/4)(2x-8) | | 11+(7+n)=24 | | -3y+8=-12x | | 4(x-2)/6=2(x+8)/13 | | 2x^2+2x=-74 | | (3/4)(4-x)=3-x | | 4(x-3)+2x=3(2x-5) | | 36x-63=36x+18 |